An integrative TAD catalog in lymphoblastoid cell lines discloses the functional impact of deletions and insertions in human genomes - Li, Chong; Bonder, Marc Jan; Syed, Sabriya; Jensen, Matthew; Human Genome Structural Variation Consortium (HGSVC); HGSVC Functional Analysis Working Group; Gerstein, Mark B.; Zody, Michael C.; Chaisson, Mark J.P.; Talkowski, Michael E.; Marschall, Tobias; Korbel, Jan O.; et al.

(untitled) (Genome Research, 2024)
The human genome is packaged within a three-dimensional (3D) nucleus and organized into structural units known as compartments, topologically associating domains (TADs), and loops. TAD boundaries, separating adjacent TADs, have been found to be well conserved across mammalian species and more evolutionarily constrained than TADs themselves. Recent studies show that structural variants (SVs) can modify 3D genomes through the disruption of TADs, which play an essential role in insulating genes from outside regulatory elements’ aberrant regulation. However, how SV affects the 3D genome structure and their association among different aspects of gene regulation and candidate cis-regulatory elements (cCREs) have rarely been studied systematically. Here, we assess the impact of SVs intersecting with TAD boundaries by developing an integrative Hi-C analysis pipeline, which enables the generation of an in-depth catalog of TADs and TAD boundaries in human lymphoblastoid cell lines (LCLs) to fill the gap of limited resources. Our catalog contains 18,865 TADs, including 4596 sub-TADs, with 185 SVs (TAD–SVs) that alter chromatin architecture. By leveraging the ENCODE registry of cCREs in humans, we determine that 34 of 185 TAD–SVs intersect with cCREs and observe significant enrichment of TAD–SVs within cCREs. This study provides a database of TADs and TAD–SVs in the human genome that will facilitate future investigations of the impact of SVs on chromatin structure and gene regulation in health and disease.